Postliberal theology and the church catholic : conversations with George Lindbeck, David Burrell, and Stanley Hauerwas - Lindbeck, George A.; Burrell, David B.; Hauerwas, Stanley, 1940-; Wright, John W. (Grand Rapids, Mich : Baker Academic, 2012)
How does postliberalism relate to Roman Catholic theology? More specifically, how reliant is postliberalism on what happened at Vatican II? This work examines the Roman Catholic roots of postliberal theology, centering on conversations with three of the most important North American theologians in the last half of the twentieth century.
Includes bibliographical references and index.
Keywords: Burrell, David B. -- Interviews; Hauerwas, Stanley, -- 1940- -- Interviews; Postliberal theology; Church -- Unity; Theologians -- United States -- Interviews